In situ 3D characterization of fatigue cracks displacement fields - Joel Lachambre; Jean-Yves Buffiere; Julien Réthoré; Arnaud Weck (Fracture and Structural Integrity)
The three dimensional growth of fatigue cracks in samples of nodular graphite cast iron is characterized using laboratory X-ray computed tomography. The cracks grow from laser machined artificial defects, their development is monitored in situ using laboratory X-ray computed tomography (lab. CT) and Digital Volume Correlation (DVC). The combination of both techniques gives access to the 3D displacement field at the tip of the crack (mainly mode I opening).